If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -2(4x + -6) = 15 Reorder the terms: 7x + -2(-6 + 4x) = 15 7x + (-6 * -2 + 4x * -2) = 15 7x + (12 + -8x) = 15 Reorder the terms: 12 + 7x + -8x = 15 Combine like terms: 7x + -8x = -1x 12 + -1x = 15 Solving 12 + -1x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 15 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 15 + -12 -1x = 15 + -12 Combine like terms: 15 + -12 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3
| 4x+16=6x+12 | | v+4y-2y+5v= | | 8x+4=(4x-3) | | 5k+6k=11 | | 10-v-17v=4 | | 3(y+2)=16(2y) | | -7h-4h-3= | | 5y^2-2=-3y | | 2-f=(f/5) | | g(x)=3x-2 | | 2-2n-4n=8 | | 5xn-18-4xn=-36 | | 3(y+2)=6(2y) | | (x/5)-12=7 | | -7x-3(-3x-20)=46 | | -8(5n+9)=11n | | 5xn-18-4xn=36 | | 2.5x+1.5=-9.5 | | 9=19x+39-4x | | 4(t-5)-3=6t-13 | | 12-3(5x-7)-4x=71 | | 0.75x+0.2x=x-2 | | 25-x=7 | | (wx)2= | | 3(8-3(1))=5(2+1) | | 7z=180-22 | | (8-3(1))=5(2+1) | | 27x^3-1= | | 9x^2-28x+3=0 | | -3p+7=6-10p-5 | | 9x+7=3x-9 | | 2r-6r=12 |